The onboard software of the EUSO‐SPB pathfinder experiment. (26th October 2018) - Fornaro, Claudio; Cafagna, Francesco Saverio; Osteria, Giuseppe; Scotti, Valentina; Perfetto, Francesco; Conti, Livio
Summary: In this paper, the flight software architecture of the EUSO‐SPB mission is described. The JEM‐EUSO program aims at developing an advanced large space‐borne UV telescope designed to detect ultra high energy cosmic rays. In this framework, the EUSO‐SPB experiment is the third pathfinder mission of the JEM‐EUSO program, the second that has been launched on a stratospheric balloon to test the technological readiness of the detectors and to carry out some preliminary scientific observations. The EUSO‐SPB software has a modular structure conceived to control all the instruments and the ancillary subsystems, to acquire data, and to manage data transfer to ground. System programming in C and C++ languages and Bash scripts have been used to implement and run the modules. The software runs on the data processor, an onboard computer that communicates with several payload blocks, the UV sensor, and the synchronization and time tagging board. The control software module controls all the subsystems, provides communication to ground through the NASA telemetry or the Internet, runs the acquisition control and download software, and manages the execution of the acquisition software. The acquisition software module directly operates the subsystems for the data acquisition activity. The acquisition control and download software module runs the acquisition software upon request of the control software and transfers scientific data to ground. The software system performed as expected during the flight on April 2017.